Follow-up of Cardiovascular Risk Following Complicated Pregnancy: a Single Centre Audit - Hughes, Katherine (Trinity Student Medical Journal, 2020)
Introduction: Gestational diabetes mellitus, pregnancy-induced hypertension and pre-eclampsia are associated with significant long-term cardiovascular and metabolic risk to the woman. Aims: The primary aim of this audit was to determine whether women who develop these pregnancy-related complications were followed up by their general practitioners (GPs) with respect to cardiovascular risk after delivery. Another aim was to assess whether the condition was communicated from the maternity health care to the GP on discharge letter. Methods: The audit was carried out using a structured search via the general practice electronic health record system. Conclusions: This audit found a deficit of follow-up monitoring of blood pressure and glucose tolerance of the women in our study and deficient communication of the complication experienced from the hospital to primary care. These findings suggest that there is a lack of appreciation of the impact of pregnancy-related cardiovascular and metabolic complications on future maternal health.